Structured Reporting of Whole-Body Trauma CT Scans Using Checklists: Diagnostic Accuracy of Reporting Radiologists Depending on Their Level of Experience - Dendl, Lena Marie; Pausch, Antonia Maria; Hoffstetter, Patrick; Dornia, Christian; Höllthaler, Josef; Ernstberger, Antonio; Becker, Roland; Kopf, Sebastian; Schleder, Stephan; Schreyer, Andreas G. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose Evaluation of the diagnostic accuracy of a checklist-style structured reporting template in the setting of whole-body multislice computed tomography in major trauma patients depending on the level of experience of the reporting radiologist.Materials and Methods A total of 140 major trauma scans with the same protocol were included in this retrospective study. In a purely trial-intended reading, the trauma scans were analyzed by three radiologists with different levels of experience (resident, radiologist with 3 years of experience after board certification, and radiologist with 7 years of experience after board certification). The aim was to fill in the checklist 1 template within one minute to immediately diagnose management-altering findings. Checklist 2 was intended for the analysis of important trauma-related findings within 10 minutes. Reading times were documented. The final radiology report and the documented injuries in the patient’s medical record were used as gold standard.Results The evaluation of checklist 1 showed a range of false-negative reports between 5.0 % and 11.4 % with the resident showing the highest accuracy. Checklist 2 showed overall high diagnostic inaccuracy (19.3–35.0 %). The resident's diagnostic accuracy was statistically significantly higher compared to the radiologist with 3 years of experience after board certification (p = 0.0197) and with 7 years of experience after board certification (p = 0.0046). Shorter average reporting time resulted in higher diagnostic inaccuracy. Most of the missed diagnoses were fractures of the spine and ribs.Conclusion By using a structured reporting template in the setting of major trauma computed tomography, less experienced radiologists reach a higher diagnostic accuracy compared to experienced readers.Key Points: Citation FormatZiel Evaluation einer strukturierten Befundung der Ganzkörper-Multislice-Computertomografie (MSCT) bei Patienten mit angenommener Polytraumatisierung anhand von Checklisten bezüglich ihrer diagnostischen Genauigkeit in Abhängigkeit der Berufserfahrung der auswertenden Radiologen.Material und Methoden In einem retrospektiven Studiendesign wurden 140 konsekutive Schockraum-CT in die Studie eingeschlossen. Diese wurden in einer Studienauswertung von 3 Radiologen (Weiterbildungsassistent im 1. Ausbildungsjahr und 2 Radiologen mit 3 und 7 Jahren Berufserfahrung als Fachärzte) mittels Checklisten ausgewertet. Checkliste 1 soll innerhalb von maximal einer Minute akut lebensbedrohliche Diagnosen und Checkliste 2 innerhalb von maximal 10 Minuten systematisch die wichtigsten Befunde erfassen. Auswertungszeiten wurden dokumentiert. Als Goldstandard dienten der schriftliche radiologische Befund und die Arztbriefe.Ergebnisse Die Auswertung von Checkliste 1 ergab zwischen 5,0 und 11,4 % falsch negative und 0,7 und 1,4 % falsch positive Befunde. Dabei wies der am wenigsten erfahrene Auswerter die höchste diagnostische Genauigkeit auf. Bei Checkliste 2 fiel eine hohe diagnostische Ungenauigkeit mit einer Falsch-Negativ-Rate zwischen 19,3 und 35,0 % auf. Die Befundgenauigkeit des Weiterbildungsassistenten war im Vergleich zu dem Facharzt seit 3 Jahren (p = 0,0197) und seit 7 Jahren (p = 0,0046) statistisch signifikant höher. Mit kürzerer Auswertungszeit stieg die Fehlerquote der Befunder deutlich an. Alle 3 Befunder übersahen am häufigsten Frakturen der Wirbelkörper und Rippen.Schlussfolgerung Unerfahrene Befunder erzielen bei Einsatz einer Checkliste zur Erfassung der wichtigsten Diagnosen von Schockraum-Patienten eine signifikant bessere Befundgenauigkeit im Vergleich mit erfahreneren Auswertern.Kernaussagen: Zitierweise
Keywords: structured reporting; CT; trauma